Souvenons-nous! - Piérard, Clovis (Paturages : Ballez-Colmant-Wuillot, 1925)
Bibliotheek Camille Huysmans
Dedicator: Piérard, Clovis, dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: Wereldoorlog 1